Turn on the Words! : Deaf Audiences, Captions, and the Long Struggle for Access - Lang, Harry G. (Book collections on Project MUSE., 2021)
"The evolution of Captioned Films for the Deaf (CFD) program is a primary focus of the book. Topics such as movie theater captioning and closed captioned television are also featured, as well as the role played by deaf community activists to improve access via captions"--